Structural basis for cholesterol sensing of LYCHOS and its interaction with indoxyl sulfate - Zhenhua Wang; Jingjing He; Yufan Yang; Yonglin He; Hongwu Qian (Nature Communications)
Abstract The lysosome serves as an essential nutrient-sensing hub within the cell, where the mechanistic target of rapamycin complex 1 (mTORC1) is activated. Lysosomal cholesterol signaling (LYCHOS), a lysosome membrane protein, has been identified as a cholesterol sensor that couples cholesterol concentration to mTORC1 activation. However, the molecular basis is unknown. Here, we determine the cryo-electron microscopy (cryo-EM) structure of human LYCHOS at a resolution of 3.1 Å, revealing a cholesterol-like density at the interface between the permease and G-protein coupled receptor (GPCR) domains. Advanced 3D classification reveals two distinct states of LYCHOS. Comparative structural analysis between these two states demonstrated a cholesterol-related movement of GPCR domain relative to permease domain, providing structural insights into how LYCHOS senses lysosomal cholesterol levels. Additionally, we identify indoxyl sulfate (IS) as a binding ligand to the permease domain, confirmed by the LYCHOS-IS complex structure. Overall, our study provides a foundation and indicates additional directions for further investigation of the essential role of LYCHOS in the mTORC1 signaling pathway.